Features OF THE FREEDOM ISSUES IN THE PLOT'S PHILOSOPHY - Sunnat kiziSunnat kizi, Rakhimdjanova Dilnavoz (International Journal of Advanced Science and Technology, 2019)
The article detailed Plotin's philosophical views, the various analysis of the concept of freedom, his interpretation of human, oneness, and intellectual freedom in the light of contemporary philosophers, and their criticisms of some flaws in Plotin's teachings. It was shown that the role of human freedom in the creation of Plotin and the issue of eternal freedom of singularity was very important. Our goal is to rely on sources and analyze Plotin's philosophical views and ideas on freedom. Plotin's Enneadas reveals a multidimensional approach to freedom.